2014
DOI: 10.1016/j.jhep.2014.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus PreS/S gene variants: Pathobiology and clinical implications

Abstract: The emergence and takeover of hepatitis B virus (HBV) variants carrying mutation(s) in the preS/S genomic region is a fairly frequent event that may occur spontaneously or may be the consequence of immunoprophylaxis or antiviral treatments. Selection of preS/S mutants may have relevant pathobiological and clinical implications. Both experimental data and studies in humans show that several specific mutations in the preS/S gene may induce an imbalance in the synthesis of the surface proteins and their consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
270
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(278 citation statements)
references
References 148 publications
5
270
0
3
Order By: Relevance
“…The presence of vaccine escape associated amino acid substitutions in the major hydrophilic region (MHR) of the HBV S gene based on previous studies was investigated [14][15][16]. In total, 24 and 103 amino acid substitutions in amplified S gene fragments were observed in the viruses isolated from the schizophrenia and control groups, respectively.…”
Section: Vaccine Escape Associated Amino Acid Substitutionsmentioning
confidence: 99%
“…The presence of vaccine escape associated amino acid substitutions in the major hydrophilic region (MHR) of the HBV S gene based on previous studies was investigated [14][15][16]. In total, 24 and 103 amino acid substitutions in amplified S gene fragments were observed in the viruses isolated from the schizophrenia and control groups, respectively.…”
Section: Vaccine Escape Associated Amino Acid Substitutionsmentioning
confidence: 99%
“…The ER plays a major role in the synthesis, folding and trafficking of secretory and membrane proteins that correlate with the cellular response known as ER stress. A considerable amount of experimental data have confirmed the potential pro-oncogenic role of preS mutated gene products via accumulation in the ER with enhanced ER stress and ROS [51] . The preS mutated proteins accumulating in the ER can trigger c-Raf-1/Erk2 signaling, which results in AP1 and NFκB activation, enhanced proliferative activity of hepatocytes and an increased incidence of liver tumors in transgenics [52] .…”
Section: Mechanisms Of Hbv-related Hcc and Oxidative Stress Involvementmentioning
confidence: 98%
“…The HCCassociated HBV variant preS has been identified in the pre-S2 start codon and/or in deletions of the 5'terminal of the preS2 region and preS1 mutation with deletions of the 3'terminal of preS1 [50,51] . These preS region mutant products induce the accumulation of mutated L protein in the endoplasmic reticulum (ER) of hepatocytes.…”
Section: Mechanisms Of Hbv-related Hcc and Oxidative Stress Involvementmentioning
confidence: 99%
“…Because the pre-S2 region includes an epitope targeted by cytotoxic T lymphocytes, type Ⅱ GGHs may represent an immune escape mutant [56] . It has also been reported that pre-S mutants could induce endoplasmic reticulum stress, followed by oxidative DNA damage and genomic instability [57,58] . Recent studies have also shown that the pre-S2 region upregulates human telomerase reverse transcriptase expression and transactivates forkhead box P3 expression, which may promote the development of HCC [59] .…”
Section: Mutationsmentioning
confidence: 99%